Assessing how emotional and social communication shapes chatbot perceived competencies - Saavedra, A.; Cortinas, M.; Rubio, N.; Loureiro, S. M. C. (AIRSI24 Proceedings Book, 2024)
The era of Artificial Intelligence (AI) has changed interactions between businesses and users, triggering fundamental inquiries into consumer behavior. Among the various applications of AI (metaverse, voice assistants, augmented reality, mixed reality, etc.), this work focuses on chatbots as conversational text assistants. A chatbot is defined as a software application that engages in a conversation with a human using natural language to respond to a consumer’s question in real-time (Rese et al., 2020). Chatbots are commonly employed by companies to interact with customers at various touchpoints throughout the customer journey, spanning different contexts such as travel, medical services, and retail (Crolic et al., 2022).